Thermal environment and microhabitat of ornate box turtle hibernacula. Issue 1 (27th July 2017) - Milanovich, Joseph R.; Struecker, Brock P.; Warcholek, Stanislaw A.; Harden, Leigh Anne
Abstract : Box turtle populations are under significant threat from historic and current alterations of land‐use where remaining populations often occur in remnant patches of suitable habitat surrounded by a heterogeneous mixture of anthropogenically altered, unsuitable habitat. Ornate box turtles Terrapene ornata are a prairie‐dependent species, are considered Near Threatened by the International Union for Conservation of Nature (IUCN), and are Endangered or Threatened within many US states. Since their range exists largely in northern latitudes, aspects of hibernacula are particularly important for winter survival. How box turtles select hibernacula within prairies is likely of great importance to better understand which microhabitats are selected for and to identify areas of suitable habitat for management purposes. Using radio telemetry in conjunction with temperature dataloggers (iButtons), we examined the phenology and thermal characteristics of box turtle hibernation, and quantified microhabitat selection of their hibernacula in remnant prairie patches. We monitored hibernation initiation/termination phenology and turtle carapace temperatures, and quantified vegetative and soil microhabitat variables of hibernacula for seven turtles in 2014/2015 and 18 turtles in 2015/2016. Box turtles initiated (descended into hibernacula) and terminated (ascended out of hibernacula) at similar time periods across two years. Although the ambient thermal environment consistently experienced temperatures below freezing, turtle hibernacula offered a buffer against those temperatures and thus the temperature of turtle carapaces never fell below freezing. Turtles selected microhabitat hibernacula with higher percentages of sand, leaf litter and bare ground, and lower percentages of clay, silt, shrubs and herbaceous ground cover. Our study suggests the phenology of box turtle hibernation may be similar across years and that hibernacula selection is driven by above‐ and belowground characteristics that ultimately lead to a more stable and warmer thermal environment.